1997
DOI: 10.1007/s004210050251
|View full text |Cite
|
Sign up to set email alerts
|

Stage duration and increase of work load in incremental testing on a cycle ergometer

Abstract: Any variation of the test protocol for incremental testing (IT) in cycle ergometry may affect the accuracy of the determination of anaerobic threshold (AnT). For lactate threshold concepts, indicating the maximum lactate steady-state (max Lass), the formation of the quasi-steady-state (QSS=95% of steady-state level) is evident. Previous studies have not specified the time that it takes for blood lactate to stabilize following incremental changes in WL. The purpose of this study was to identify the minimum dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
2
18
1
3
Order By: Relevance
“…Blood lactate concentrations were plotted against power and the lactate thresholds determined by linear regression breakpoint analysis (12). A previous study demonstrated that a 20 W/3-min workload increase is the most appropriate for the identification of lactate thresholds due to the blood lactate kinetics (13).…”
Section: Progressive Testmentioning
confidence: 99%
“…Blood lactate concentrations were plotted against power and the lactate thresholds determined by linear regression breakpoint analysis (12). A previous study demonstrated that a 20 W/3-min workload increase is the most appropriate for the identification of lactate thresholds due to the blood lactate kinetics (13).…”
Section: Progressive Testmentioning
confidence: 99%
“…Collectively, the present studies provide a significant contribution to a limited body of recommendation for accurately determining LT2 is consistent with others [16,283,284] , and supported by the results of this thesis that show LT2 elicited a V O2, heart rate, [La -] and (albeit inconsistently) power output that was similar 279 to those elicited during 40 km cycling time trials. Thus, its validity for establishing a performance intensity was confirmed.…”
Section: Practical Implicationssupporting
confidence: 72%
“…The study of Bishop et al [10] reported stage durations of 3 min, 162 however it has been concluded that stages shorter than 5 min may over-predict LT2. and therefore an accurate determination of LT2 [282][283][284] . The study of Fell [18] reported a larger variation in LT2 power output (260 ± 42 W) than the present study (238 ± 28 W), and larger variation is known to result in stronger relationships with endurance performance [1] .…”
Section: Correlations With 40 Km Time Trial Performancementioning
confidence: 99%
“…De acordo com o estudo de Stockhausen et al (1997), seriam necessários mais de 2 minutos de carga para um incremento acima de 10 W para a obtenção do estado quase estável do lactato sanguíneo, possibilitando a determinação adequada do limiar de lactato.…”
Section: Ab -Lvfc Lvfc Ac -Lvfcunclassified
“…Dessa forma, pode-se observar que o critério recomendado de Beneke (2003) é mais rigoroso que o de Stockhausen et al (1997) e menos rigoroso que o de Heck et al (1985).…”
Section: Ab -Lvfc Lvfc Ac -Lvfcunclassified